Transformations of Ontology: Form and Negativity - Šerpytytė, Rita (Problemos, 2016)
The paper raises the question whether and to what extent is it possible to talk, on the one hand, about the identity of ontology, and, on the other hand, about its transformations. This problem is discussed by reconstructing the concept of plasticity in Malabou’s philosophy. Such reconstruction is carried out by focusing on the relationship between form and negativity, which is quintessential for the same idea of plasticity. It is shown that the analysis of plasticity as an annihilating power of form in Malabou’s philosophy is based on the separation of two negations – dialectical and differential (deconstructive) one. However, such an analysis does not disclose the difference between logical and ontological aspects of negation (negativity). Meanwhile, taking into account the logical and ontological non-identity of negation (negativity), the main task is not to consider dialectics in opposition to differànce, but rather to examine the very question of relationship between the dialectical and nihilist strategies. This insufficiently articulated and controversial approach to the relationship between dialectics and negation becomes, in Malabou’s philosophy, the open problem of the very form of plasticity. The reconstructive analysis of Malabou’s philosophy directed to the relationship between form and negativity, reveals the transformability and metamorphability focused on philosophical form – concept. However, for Malabou, transformation never destroys identity, but just confirms it.